Design a sensor amplifier for real-time monitoring and remote sensing - Wong, Jarell Zi Jian (Nanyang Technological University, 2022)
The Internet of Things (IoT) has gained traction over the years. To reduce costs, Universal Sensor Amplifiers have gained traction. However, much research has been focused on sensors with a time-varying Direct Current (DC) output. This project proposes a sensor amplifier that can further reduce costs by allowing support for all types of sensors. The sensor amplifier was designed, built and tested successfully.